Pengaruh Pemberian Tablet Fe Saat Menstruasi Mencegah Penurunan Kadar Hemoglobin - Novia Arum; Sadiman Sadiman; Riyanto Riyanto (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2018)
Background: Increasing baby's growth and development can be done by providing stimulation, such as massage. Baby massage is beneficial to increase baby's weight. The monthly report of the Ganjar Agung Health Center in January-March 2017 contains an average of 14.7% of babies who do not gain weight. Purpose: The study aims to determine the effectiveness of infant massage on weight gain in infants aged 0-3 months in the Ganjar Agung Metro Barat Health Center in 2017. Methods: This study uses a pre-experimental design with non-equivalent control group design. The intervention given is baby massage. The research sample was all infants aged 0-3 months totaling 25 babies taken by consecutive sampling technique. Data analysis using paired t test. Results: The results showed a mean increase in baby's body weight after massage of 0.916 kg (SD 0.1214kg) and there was an effect of infant massage on weight gain in infants aged 0-3 (p = 0.000). Conclusion: The conclusion of the study is that infant massage can be one of the interventions to increase the baby's weight. Efforts to socialize baby massage programmatically need to be improved as one of the interventions to increase the growth (weight) of the baby.